Conceptions of the particle model held by preservice elementary science teachers. - Thorne, Barbara Margaret (My University, 1990)
The purpose of this study was to determine some of the alternative conceptions held by preservice elementary teachers with respect to the particle model of matter. The sample selected for the study was composed of populations of student teachers completing science mehodology courses at the Johannesburg College of Education (JCE). (Abbreviation abstract)
A Research Report Submitted to the Faculty of Science University of the Witwatrsrand, Johannesburg. in Part Fulfilment of the Requirements for the Degree of Master of Sclence.
Keywords: Science -- Study and teaching (Elementary) -- South Africa.; Science -- Methodology -- Study and teaching.; Chemistry -- Methodology -- Study and teaching.; Particles -- Study and teaching (Elementary); Matter -- Constitution.; Matter -- Properties.